The Contribution of Histone Crotonylation to Tissue Health and Disease: Focus on Kidney Health - Martinez-Moreno, Julio M.; Fontecha-Barriuso, Miguel; Martín-Sánchez, Diego; Sánchez-Niño, Maria D.; Ruiz-Ortega, Marta; Sanz, Ana B.; Ortiz, Alberto (Frontiers in Pharmacology, 2020)
Acute kidney injury (AKI) and chronic kidney disease (CKD) are the most severe consequences of kidney injury. They are interconnected syndromes as CKD predisposes to AKI and AKI may accelerate CKD progression. Despite their growing impact on the global burden of disease, there is no satisfactory treatment for AKI and current therapeutic approaches to CKD remain suboptimal. Recent research has focused on the therapeutic target potential of epigenetic regulation of gene expression, including non-coding RNAs and the covalent modifications of histones and DNA. Indeed, several drugs targeting histone modifications are in clinical use or undergoing clinical trials. Acyl-lysine histone modifications (e.g. methylation, acetylation and crotonylation) have modulated experimental kidney injury. Most recently, increased histone lysine crotonylation (Kcr) was observed during experimental AKI and could be reproduced in cultured tubular cells exposed to inflammatory stress triggered by the cytokine TWEAK. The degree of kidney histone crotonylation was modulated by crotonate availability and crotonate supplementation protected from nephrotoxic AKI. We now review the functional relevance of histone crotonylation in kidney disease and other pathophysiological contexts, as well as the implications for the development of novel therapeutic approaches. These studies provide insights into the overall role of histone crotonylation in health and disease.